The Application of the Casework Method in Handling Neglected Elderly Individuals at the Social Protection Home of Medan City - Carcyela Octa Sihite (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the social work intervention process for a neglected elderly client at the Social Protection Home of Medan City, analyze the implementation of a case work method based on the strengths-based approach, and identify changes following the intervention. A qualitative case study design was employed. Data were collected through in-depth interviews, observation, documentation, and BPSS (Biological, Psychological, Social, Spiritual) assessment. The intervention followed the stages of engagement, intake, contract, assessment, planning, intervention, evaluation, and termination. The findings revealed that the client experienced physical limitations, low motivation, limited family support, and restricted social interaction. The strengths-based approach helped identify the client’s strengths and potential, while Motivational Interviewing enhanced intrinsic motivation and self-confidence. Evaluation using the CIPP model showed that the intervention was appropriate to the client’s needs and resulted in improved motivation, social participation, and psychological well-being. The study highlights that integrating case work, the strengths-based approach, and Motivational Interviewing is effective in improving the social functioning of neglected older adults.